Immunohistochemical Detection of FLAG-Tagged Endogenous Proteins in Knock-In Mice. (April 2015) - Ferrando, Ronald E.; Newton, Kim; Chu, Felix; Webster, Joshua D.; French, Dorothy M.
With recent advances in immunohistochemical (IHC) techniques, immunohistochemistry now plays a more important role in research, especially in mouse models where characterization of cellular patterns of protein expression has become critical. Even with these recent advances, a paucity of IHC quality antibodies for some proteins still exists. To address this, we have developed a novel IHC assay that utilizes a commercially available goat anti-DDDDK peptide polyclonal antibody on paraffin-embedded tissues from knock-in mice expressing proteins of interest tagged with a 3×FLAG epitope at physiologically relevant levels. Focusing on two 3×FLAG-tagged proteins for which specific antibodies were available, USP48 and RIPK3, we were able to validate our anti-DDDDK assay by comparing the IHC directed against the actual proteins to the anti-DDDDK IHC assay, which recognizes the FLAG epitope. We were also able to detect a third 3×FLAG-tagged protein, BAP1, for which quality reagents were not available. This universal IHC method will enable researchers to characterize the expression patterns of proteins of interest when specific antibodies are lacking.